Growth and Standing Volume Estimation of Cedrus deodara (Roxb.) Loud. Stands under the Present System of Management in Himachal Himalayas - a Case Study - Singh, Ashok; Gupta, N. K. (Indian Forester, 2008)
The present study on management of Cedrus deodara under shelter wood system is aimed at drawing attention for long sustenance of management practices. The study reflects some useful facts. The parameters like diameter, height, bole height and crown width increased with the increase in diameter of trees, however, number of individuals show decreasing trend with the diameter. Occurrence of broad leaved species in PBIV creating completion for establishment of main crop ultimately into less individuals. The variation in crop height was comparatively low (with 17.71 m minimum in PBIII and maximum of 22.92 m in PBI) in different PBs. The higher crop height in PBIV in comparision to PBIII was due to the presence of higher sized trees in PBIV and which were not removed in final felling thus affected the regeneration and growth of main crop. Mean crop basal area and crop standing volume was maximum in PBI, followed by PBII, PBIII and PBIV. The maximum basal area and standing volume was higher in diameter classes of crop diameter in PBII and PBIII, where crop was in proper distribution. The maximum total standing volume was recorded in PBI, showing sufficient tree density requires initiation for seeding felling treatment. Crop bole height and Crop crown width was maximum in PBII, followed by PBI, PBIII and PBIV. The correlation between different tree parameters of deodar was positive and significant. Standing volume of deodar trees can be well estimated by using diameter, height, crown width and bole height as independent variables using linear and log linear models. In a nutshell, the present system of management requires continuous monitoring for sustain yield regulation in connection with demand, supply and environment equilibrium.